Принципи методу групового урахування аргументів в контурі системного аналітичного проекту - Осипенко, В.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
This work is continuation of development direction begun [10]. The general chart of the inductive planning of analytical problem decision with application in the contour of project of principles of GMDH is presented. In particular there are principle of external addition for evaluation of intermediate results and inductive increasing of informative base complication due to use of the information monitoring. The analytical planning foresees also application of the systems analysis methodology in both parts of intermediate results synthesis and forming of the final result as well. The example of application of offered approach is briefly described the decision-making about acquisition of filling stations network.